Family Caregivers Challenges for Stroke Survivors in the Community: A Literature Review - Israfil, Israfil; Wulandari, Sarah Kartika; Suyasa, I Gede Putu Darma; Indrayani, Ni Luh Dwi; Agustini, Ni Luh Putu Inca Buntari (MEDICA (International Medical Scientific Journal), 2026)
Stroke is a chronic condition that significantly reduces the patient's quality of life and increases the need for support from family caregivers. This situation places the family as a crucial element in patient care, yet often presents significant challenges for family caregivers. This study aims to identify and describe the various challenges faced by families caring for stroke patients in the community. A literature review design was employed. Relevant articles published between 2020 and 2025 were retrieved from international databases including PubMed and ScienceDirect, using the keywords "family challenges" OR "family burden" AND "stroke" OR "stroke survivor." The inclusion criteria were determined using the PEO framework. A total of 346 articles were identified, and fifteen articles met the inclusion criteria for the review. The findings indicate that family caregivers of stroke patients face various challenges due to the complex demands of care, ranging from emotional stress at the time of diagnosis to physical and social challenges during home care. Challenges are further exacerbated when the patient experiences dysphagia, severe disability, or psychological problems such as depression and anxiety. Factors contributing to these challenges include the family caregiver's employment status, educational level, kinship relationship, social support, knowledge of stroke rehabilitation, the transition process from hospital to home, limited access to healthcare, and limited social activities. Caring for stroke patients presents significant challenges for families, who serve as the primary caregiver system and play a central role in community care. Interventions that support family caregivers through education, psychosocial support, and access to adequate health and rehabilitation services are crucial for community nurses to reduce caregiver burden and improve the quality of life for both family caregivers and stroke patients in the community.